Emerging Evidence of Epigenetic Modifications in Vascular Complication of Diabetes - Khullar, Madhu; Cheema, Balneek Singh; Raut, Satish K. (Frontiers in Endocrinology, 2017)
Genes, dietary and lifestyle factors have been shown to be important in the pathophysiology of diabetes and associated microvascular complications. Epigenetic modifications such as DNA methylation, histone acetylation and post-transcriptional RNA regulation are being increasingly recognized as important mediators of the complex interplay between genes and the environment. Recent studies suggest that diabetes induced dysregulation of epigenetic mechanisms resulting in altered gene expression in target cells can lead to diabetes associated complications, such as diabetic cardiomyopathy, diabetic nephropathy, retinopathy etc. which are the major contributors to diabetes associated morbidity and mortality. Thus knowledge of dysregulated epigenetic pathways involved in diabetes can provide much needed new drug targets for these diseases. In this review, we constructed our search strategy to highlight the role of DNA methylation, modifications of histones and role of non-coding RNAs (microRNAs & long non coding RNAs) in vascular complications of diabetes including cardiomyopathy, nephropathy and retinopathy.